2014
DOI: 10.3382/ps.2013-03587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary clays on performance and intestinal mucus barrier of broiler chicks challenged with Salmonella enterica serovar Typhimurium and on goblet cell function in vitro

Abstract: In vivo and in vitro experiments were conducted to test for beneficial effects of dietary clays on broiler chicks challenged with Salmonella enterica serovar Typhimurium and to explore potential mechanisms. First, two hundred forty 1-d-old male broilers (initial BW: 41.6 ± 0.4 g) were allotted in a 2 × 4 factorial arrangement in a randomized complete block design. There were 2 infection treatments (with or without Salmonella) and 4 diets: basal (BAS), 0.3% smectite A (SMA), 0.3% smectite B, and 0.3% zeolite. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Intestinal goblet cells in the intestinal tract secrete mucus and trefoil factor (TFF) 3 to form the first line of defense in the mucosa; Paneth cells are an important source of antimicrobial peptides in the intestine; and tuft cells regulate type 2 immune responses through the secretion of IL‐25 to protect the mucosa against helminth infection . S. typhimurium infection stimulates the hyperplasia of goblet, Paneth, and tuft cells, which is the normal host protective mechanism against epithelial damage caused by pathogen invasions . To simultaneously avoid over‐exhaustion and exert anti‐inflammatory functions, Lactobacillus modulated the expression of AMP (defa1, reg3g, muc2) and the number of AMP‐secreting cells to a more reasonable level, and this finding was confirmed by a normal intestinal structure and a typical organoid morphology.…”
Section: Discussionmentioning
confidence: 83%
“…Intestinal goblet cells in the intestinal tract secrete mucus and trefoil factor (TFF) 3 to form the first line of defense in the mucosa; Paneth cells are an important source of antimicrobial peptides in the intestine; and tuft cells regulate type 2 immune responses through the secretion of IL‐25 to protect the mucosa against helminth infection . S. typhimurium infection stimulates the hyperplasia of goblet, Paneth, and tuft cells, which is the normal host protective mechanism against epithelial damage caused by pathogen invasions . To simultaneously avoid over‐exhaustion and exert anti‐inflammatory functions, Lactobacillus modulated the expression of AMP (defa1, reg3g, muc2) and the number of AMP‐secreting cells to a more reasonable level, and this finding was confirmed by a normal intestinal structure and a typical organoid morphology.…”
Section: Discussionmentioning
confidence: 83%
“…24 In vitro, lipopolysaccharide (LPS) could induce the increase of RELM b mRNA expression in LS174T cells similar to Goblet cells. 25 It is suggested that RELMb can be a good marker for early diagnosis of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then treated with GOS for 96 h. At the end of incubation, cells were scraped from culture plates and lysed with 400 μL of 1× Cell Lysis Buffer (Cell Signaling Technology Inc., Danvers, MA) with protease inhibitor cocktail (Sigma Aldrich Co., St. Louis, MO). Immunoblotting was performed as described earlier . The bound proteins were probed with the following primary antibodies: RELMB (rabbit anti‐human at a dilution 0.2 μg/mL; Peprotech, Rocky Hill, NJ), CHST5 (mouse monoclonal antibody at a dilution of 3μg/mL; Abnova, Taipei, Taiwan), TFF3 (mouse monoclonal antibody at a dilution of 2 μg/mL; R&D Systems, Minneapolis, MN), β‐actin (mouse monoclonal antibody at a dilution of 1:2000; Santa Cruz Biotechnology, Santa Cruz, CA) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%